ANALISIS KUALITAS PELAYANAN PAS BANDARA INTERNASIONAL NGURAH RAI DENGAN MENGGUNAKAN MODEL SERVQUAL - Suska V, I Made; Budiartha R. M., N.; Astawa Diputra, Gd. (JURNAL SPEKTRAN, 2013)
Permit to a person to enter the restricted area at Ngurah Rai Airport which is called Airport Pas can be given in accordance with the duties and activities of a person at the airport. On permit service, there are disappointments and complaints of the Pas applicant that can still be found in the Pas service like duration of Pas completion and officer service at the time of application. The different perception and expectation of Pas applicant must remain in the regulation corridors and prioritize security at airports. The purpose of this research is assesing the quality of Pas service in the Airport Authority Region IV by using a SERVQUAL (Service Quality) model. The model is comparing the two main factors, namely real customer perception of the service that they received (Perceived Service) with the actual services expected/desirable (Expected Service) which consists of 5 (five) dimensions, those are Tangibles (physical), Reliability, Responsiveness, Assurance and Empathy (attention). By using these models, it is known that the quality of Pas service in the Airport Authority Region IV is still less than the expectations of the applicant and the most important dimension to enhance is Responsiveness. Gaps between perception and expectation as follows: Responsiveness (-0,2240), Assurance (-0,2171) , Reliability (-0,2099) , Tangibles (-0,1994) , dan Empathy (-0,1373).
Keywords: Pas, Servqual, Perceptions, Expectations, Airport Authority Region IV